2017
DOI: 10.1007/s10549-017-4435-x
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole synergizes with paclitaxel to inhibit cell growth and induce apoptosis in triple-negative breast cancer

Abstract: All TNBC cells tested responded synergistically to riluzole and paclitaxel strongly suggesting the usefulness of this combinatorial treatment strategy in TNBC, especially for patients whose tumors are relatively resistant to paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 33 publications
(48 reference statements)
5
30
1
1
Order By: Relevance
“…Our data demonstrate that riluzole can display synergistic anti-GBM effects with mTOR inhibitors (see Figure 5C) and recent data have demonstrated that riluzole synergizes with the chemotherapeutic paclitaxel in triple-negative breast cancers [53]. It is well known that chemotherapeutically induced cellular stress can activate IRES-mediated protein synthesis of various transcripts, including the aryl hydrocarbon receptor, ATF2, ribosome binding protein 1, c-myc and β-catenin [54][55][56][57][58].…”
Section: Discussionsupporting
confidence: 74%
“…Our data demonstrate that riluzole can display synergistic anti-GBM effects with mTOR inhibitors (see Figure 5C) and recent data have demonstrated that riluzole synergizes with the chemotherapeutic paclitaxel in triple-negative breast cancers [53]. It is well known that chemotherapeutically induced cellular stress can activate IRES-mediated protein synthesis of various transcripts, including the aryl hydrocarbon receptor, ATF2, ribosome binding protein 1, c-myc and β-catenin [54][55][56][57][58].…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, the response of xenograft to riluzole monotherapy was minimal. To add, our observations do not agree with another report which proposed that breast cancer xenografts treated with riluzole had a significant decrease in tumor volume [14]. However, several differences exist between this report and our work.…”
Section: Discussioncontrasting
confidence: 99%
“…International Publisher response of cancer to different anti-tumor treatments, including chemotherapy and radiotherapy [13][14][15][16].…”
Section: Ivyspringmentioning
confidence: 99%
“…After 24 hours, riluzole had no significant effect on CXCL1 levels in any cell line. This is consistent with microarray analysis performed previously with riluzole-treated MDA-MB-231 cells 24 . By 48 hours, a dose-dependent increase in CXCL1 was observed in all 3 cell lines with a significant increase of over 3-fold in SUM159 and BT549 cells after treatment with the highest dose (50 μM).…”
Section: Resultssupporting
confidence: 92%